Association between Muscle Mass and Muscle Strength with Physical Performance in Elderly in Surabaya - Kristiana, Titin; Widajanti, Novira; Satyawati, Rwahita (Surabaya Physical Medicine and Rehabilitation Journal, 2020)
ABSTRACTBackground: Sarcopenia is a decrease in muscle mass and strength that mostly happens in the elderly. Sarcopenia is a problem that is often found in the elderly who are at risk of disability, hospitalization and death. This data on muscle mass and strength with physical performance is expected to support the theory of sarcopenia and as a reference in promoting and preventing sarcopenia in elderly.Aims: To analyze the association between muscle mass and strength (handgrip strength) with physical performance assessed using Short Physical Performance Battery (SPPB) in an elderly community.Methods: This study was a cross-sectional observational analytic study involving 203 sample of elderly (age >60 years old). The subjects were categorized as the strong and weak muscle mass and muscle strength, also the high, moderate and low physical performance. We used Bioimpedance Analysis (BIA) and hand dynamometer to measure muscle mass and muscle strength (handgrip strength). SPPB was used to assess physical performance.The association between muscle mass and strength with physical performance was displayed in bivariate analysis with chi square.Result: Of all 203 subjects, 57 were males and 146 were females. Chi square test showed association between muscle strength (handgrip strength) with physical performance (SPPB) (p=0.001), with a weak correlation (r=0.26) and no association between muscle mass and physical performance (SPPB) (p=0.517).Conclusion: There is a positive association between muscle strength with physical performance, with a weak correlation and no association between muscle mass and physical performance in the elderly community in Surabaya.